Physicochemical Characterisation and Flocculation Analysis of a Novel Cationic Chitosan-Like Bioflocculant from Citrobacter Youngae GTC 01314 to Improve Sludge Dewatering - Mohamed Hatta, Nur Syahirah (Curtin University, 2021)
Bacterial strains from the genus Citrobacter are proven to be cultivated effectively in acetate medium to produce chitosan-like bioflocculants with strong flocculation activity. Selected physicochemical characteristics and flocculation behaviour of a novel bioflocculant from Citrobacter youngae GTC 01314 were studied in kaolin suspension, followed by evaluation of its dewatering performance in activated sludge sample. The results confirmed the effectiveness of the bioflocculant in enhancing sludge dewaterability which advocates its potential application in water and wastewater treatment.